2016
DOI: 10.2147/dddt.s108185
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oral bioavailability of acetylpuerarin by poly(lactide-co-glycolide) nanoparticles optimized using uniform design combined with response surface methodology

Abstract: Acetylpuerarin (AP), an acetylated derivative of puerarin, shows brain-protective effects in animals. However, AP has low oral bioavailability because of its poor water solubility. The objective of this study was to design and develop poly(lactide-co-glycolide) (PLGA) nanoparticles (NPs) to enhance the oral bioavailability of AP. The NPs were prepared using a solvent diffusion method optimized via uniform design (UD) combined with response surface methodology (RSM) and characterized by their morphology, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…(2) The ME system might facilitate intestinal cellular uptake and lymphatic transport, which could contribute to the enhancement of lycopene absorption (Tang et al., 2013; Bala et al., 2016). (3) Tween 80 and Transcutol HP could exert synergistically as inhibitors of P-glycoprotein multidrug efflux system (Takahashi et al., 2002; Sun et al., 2016), which is mainly localized in the columnar epithelial cells of the lower gastrointestinal tract (Zakeri-Milani & Valizadeh, 2014). Thus, these microemlusion excipients could potentially enhance oral bioavailability of lycopene.…”
Section: Discussionmentioning
confidence: 99%
“…(2) The ME system might facilitate intestinal cellular uptake and lymphatic transport, which could contribute to the enhancement of lycopene absorption (Tang et al., 2013; Bala et al., 2016). (3) Tween 80 and Transcutol HP could exert synergistically as inhibitors of P-glycoprotein multidrug efflux system (Takahashi et al., 2002; Sun et al., 2016), which is mainly localized in the columnar epithelial cells of the lower gastrointestinal tract (Zakeri-Milani & Valizadeh, 2014). Thus, these microemlusion excipients could potentially enhance oral bioavailability of lycopene.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the release profile of nano amoxicillin in simulated gastrointestinal environment emerged in two stages: first as a rapid burst effect and, then as a relatively slow release. The rapid release (within 1.5 hr) is thought to be associated with the drug which is absorbed or weakly bound to the surface area of the nps, while the slow release is thought to be associated with the release of the remaining portion of the drug that mostly trapped in the nps (Parsian et al., ; Sun et al., ). Although the results of in vitro drug release studies were evaluated within a limited period (24 hr), it was determined that amoxicillin nps has a relatively low (~2.5‐fold) initial burst release rate compared to free amoxicillin and its total cumulative release rate is 51.96% in 24 hr.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation of this situation could be that the faster migration of the weakly localized or bound drug molecules on the surface of particles. The subsequent slow release is likely due to slower migration of the remaining drug entrapped in the inner region of the particles [43,44].…”
Section: In Vitro Drug Releasementioning
confidence: 99%